Pengaruh Manajemen Sumber Daya Manusia dan Penerapan Good Manufacturing Practices Terhadap Peningkatan Higiene Produksi: Studi Pada Karyawan Bakpia Kukus Tugu Jogja Divisi Produksi dan Quality Control - Zulia Pranita Sari; Niken Widyastuti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of Human Resource Management and Good Manufacturing Practices on Improving Production Hygiene, with the research focused on employees of Bakpia Kukus Tugu Jogja. The problems that often occur are the ineffectiveness of implementing hygiene standards and weaknesses in the human resource management system which are the important basis for conducting this research. This study uses a quantitative approach with a survey method by distributing questionnaires to 102 respondents who are employees of Bakpia Kukus Tugu Jogja in the production and quality control divisions. Data analysis was carried out using multiple linear regression with the help of SPSS software version 25.